"Stripping" the Carbon Atom of Methyl Halide by a Cationic Holmium Complex: A Gas‐Phase Study. Issue 41 (25th August 2015) - Zhou, Shaodong; Schlangen, Maria; Li, Jilai; Wu, Xiao‐Nan; Schwarz, Helmut
Abstract Mechanistic aspects of an unusual reaction of [HoC6H4S]+ with CH3X (X=Cl, Br, I) have been investigated using Fourier‐transform ion cyclotron resonance mass spectrometry combined with density functional theory (DFT) calculations. In this thermal process, all four bonds of the methyl halides are cleaved.